2000
DOI: 10.1136/jech.54.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Height and risk of death among men and women: aetiological implications of associations with cardiorespiratory disease and cancer mortality

Abstract: Objectives-Height is inversely associated with cardiovascular disease mortality risk and has shown variable associations with cancer incidence and mortality. The interpretation of findings from previous studies has been constrained by data limitations. Associations between height and specific causes of death were investigated in a large general population cohort of men and women from the West of Scotland. Design-Prospective observational study. Results-Over the follow up period 3347 men and 2638 women died. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
173
2
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(193 citation statements)
references
References 40 publications
(25 reference statements)
12
173
2
1
Order By: Relevance
“…Six other prospective studies Chute et al, 1991;Bostick et al, 1994;Giovannucci et al, 1995;Robsahm and Tretli, 1999;Smith et al, 2000), but not all, support our finding that being tall significantly elevates the risk of colorectal cancer. One possibility is that taller people may have longer intestines (Hirsch et al, 1956) and have a greater rate of cell division within the tissue (Albanes and Winick, 1988); thus, more colon cells may be at risk.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Six other prospective studies Chute et al, 1991;Bostick et al, 1994;Giovannucci et al, 1995;Robsahm and Tretli, 1999;Smith et al, 2000), but not all, support our finding that being tall significantly elevates the risk of colorectal cancer. One possibility is that taller people may have longer intestines (Hirsch et al, 1956) and have a greater rate of cell division within the tissue (Albanes and Winick, 1988); thus, more colon cells may be at risk.…”
Section: Discussionsupporting
confidence: 80%
“…Height is affected not only by genetic factors, but also by nutritional condition during childhood and adolescent. Some studies Chute et al, 1991;Bostick et al, 1994;Giovannucci et al, 1995;Robsahm and Tretli, 1999;Smith et al, 2000), but not all (Okasha et al, 2000), have reported a positive association between height and colon cancer. Results of studies on body mass index (BMI) in relation to colorectal cancer have been also inconsistent.…”
mentioning
confidence: 99%
“…The majority of cohort studies have found that tall stature is associated with increased cancer risk. The most consistent associations are found for breast cancer, a recent review finding that all but one (Davey Smith et al, 2000) of 24 prospective studies showed a positive association with height (Gunnell et al, 2001).…”
mentioning
confidence: 76%
“…In our study, short stature showed an association with decreased DBP in women. However, most studies have not observed a relation between height and DBP, 5,7-11,13,14 except for one study that found an inverse relation between height and DBP in men, 4 and another study that found a direct relation. 30 These inconsistent results could be due to the fact that adult height is a nonspecific measure of exposures that affect all growth periods and not just growth in childhood.…”
Section: Pulse Systolic and Diastolic Blood Pressure In Older Peoplementioning
confidence: 99%
“…16,17 The independent association of short stature with increased PP suggests that PP could be a potential mediator of the relation between short stature and increased risk of coronary heart disease that has been seen in many studies. 4,19 This would also explain the paradox of the consistent findings about the relation between height and coronary heart disease and the inconsistent findings about the association of short stature with SBP and DBP.…”
Section: Pulse Systolic and Diastolic Blood Pressure In Older Peoplementioning
confidence: 99%